Immune checkpoint blockade in small cell lung cancer. (November 2019) - Tay, Rebecca Y.; Heigener, David; Reck, Martin; Califano, Raffaele
Highlights: Immune checkpoint blockade represents a promising treatment in SCLC. Comprehensive review of anti-PD-(L)1 and anti-CTLA-4 agents in SCLC presented. Biomarkers under investigation are PD-L1 expression and tumour mutational burden. Strategies to enhance immune responses and refine patient selection are needed. Abstract: Despite the highly immunogenic potential of small cell lung cancer (SCLC), progress in evaluating the therapeutic value of immune checkpoint agents has lagged behind that of non-small cell lung cancer. Results from a number of phase I-III clinical trials that specifically address the use of anti-PD-1, anti-PD-L1 and anti-CTLA-4 agents in SCLC have now been reported. This review will focus on the available evidence for immune checkpoint blockade in SCLC and review current biomarker strategies with the aim of providing perspective and interpretation of this data for clinical practice.